Evaluation of the Archival, Library and Information Studies Department eClass at University of West Attica - Koulouris, Alexandros (Journal of Integrated Information Management, 2019)
Purpose - This paper presents and discusses the main results of a survey concerning students and faculty (academic staff) evaluation of the eClass of the Department of Archival, Library & Information Studies, University of West Attica, with the use of online questionnaire. The survey was conducted in October 2019 and it is a comparative study of a previous research-survey (about the eClass) of 2012. Design/methodology/approach - The questionnaire, consisted of open and closed-ended questions, and were sent respectively to the undergraduate and postgraduate students and the faculty’s staff (or professors) of the Department. As a result, 275 valid answers (233 undergraduates and 42 postgraduates’ valid responses) translated to a net response rate of 39%, while the faculty survey returned 29 valid answers with a 100% participation rate. Findings - The findings demonstrate that the students and the faculty agree that the eClass is essential for the Department’s courses and program (undergraduate and postgraduate). The communication and the interactions between the eClass platform and the users (faculty and students) has been very well established. Finally, the more interesting result that revealed from the regression analysis that was conducted, is that the more recent registration by the users (student and faculty), the more they visit the platform (eClass) and the higher they appreciated the system’s functionalities aspect. Originality/value – Useful findings were extracted regarding the evaluation of ALIS Dept eClass, after (almost) ten years of implementation. Useful comparison was made with the previous evaluation in 2012 and joined results extracted. The opinions gathered from the undergraduate and postgraduates’ students, and the faculty, reveal that the strategic goal of the ALIS Dept to use the eClass as a centralized component for the studies in the Dept, is a sophisticated choice.